Implementasi Pemungutan Retribusi Daerah Bidang Persampahan Dan Kebersihan Berdasarkan Peraturan Daerah Nomor 15 Tahun 2011 Kabupaten Indragiri Hilir - Muhsin Muhsinhukum (Fakultas Hukum Universitas Islam Indragiri, 2021)
Efforts to implement the implementation of the Regional Regulation regarding the retribution for waste and sanitation services in Indragiri Hilir Regency certainly require support from many parties, both from the local government and the community who are classified as obligatory levies. The problems in this study are (1) How is the Implementation of Collection of Regional Retribution in the Sector of Waste and Cleanliness Based on Regional Regulation Number 15 of 2011 Indragiri Hilir Regency, (2) What are the Inhibiting Factors in the Implementation of Collecting Regional Levies in the Sector of Waste and Cleanliness Based on Regional Regulation Number 15 of 2011 Indragiri Hilir Regency. (3) What are the Efforts in Implementing Regional Retribution Collectors in the Sector of Waste and Cleanliness Based on Regional Regulation Number 15 of 2011 Indragiri Hilir Regency This research method uses empirical/sociological legal research, the nature of this research is descriptive, that is, it provides a clear picture. It can be concluded that (1) Implementation of Collection of Regional Levies in the Sector of Waste and Cleanliness Based on Regional Regulation No. 15 of 2011 Indragiri Hilir Regency begins with collecting data and mandatory registration of user fees clearly and correctly and collecting using SKRD which is carried out once a month turns into two times in one month. month. (2) Inhibiting factors in this implementation can be seen from the lack of supervision, factors from the law itself, law enforcement factors, facilities and facilities and community factors. (3) Efforts are made by increasing the supervision carried out by DLHK together with Bapenda, issuing regulations further implementing regulations as a basis for implementing additional regulations, involving Satpol PP who act as regional regulations enforcers and the formation of PPNS as part of investigators who are authorized to take action on cases of regional regulations violations committed by retribution obligations that do not implement regulations.